Brand Self-distance vs Brand-self Approach: Multiple Relationships Between Consumers and Brands - Loureiro, S. M. C.; Lopes, R. (Advances in Psychology Research, 2015)
A considerable work has been done in academia regarding positive emotions and favorable relationships with brands which lead to positive responses and even loyalty. Nevertheless, if consumers can have real feelings of love towards a brand, is very likely that consumers can also have real feelings of hate. Actually, consumers could love some brands, be indifferent or express negative opinions towards other brands (Khan and Lee, 2014). Ahuvia (1993) argues that consumers can have real feelings of love toward an object and conceptualize the love as having two dimensions: real and desired integration. Could this assumption be employed to real feeling of hate towards a brand? Developing a field of knowledge on negative relationships presents a challenge. Whatever the results might be, negative relationships would definitely operate under different and yet weak assumptions and pose different questions, as suggested by Fournier and Alvarez (2013). The purpose of this chapter is to contribute to this discussion presenting an overview of the research concepts and main theories employed in several previous studies to express negative consumer brand relationships (NCBR), based on a systematic literature review. Consequently, the chapter identifies four fundamental key thematic themes of NCBR: conflict attitude, brand-self distance, negative perceived emotions, and countercultural phenomena and proposes a conceptual framework on NCBR. The chapter concludes with suggestions for further studies and presents some preliminary empirical results from the first seminal studies.